Jajanan sehat bagi anak-anak berorientasi pangan fungsional berbahan dasar ikan laut - Sri Handayani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
The purpose of this study was to study the characteristics of caught marine fish at the study site, and to apply the marine fish caught at the study site in the form of healthy snacks, specifically children's snacks. The results of this study indicate that 15 species of fish caught in the Madura strait were 15 types, namely Talang-Talang (Queenfish), Tongkol Lurik (Euthynnus affinis), Tenggiri (Scomberomorus ommerson), Mackerel Board (Scomberomorus, Alu-Alu (Sphyraena barracuda), Banyar (Rastreligger kanagurta), White Kakap (L. calcarifer), Red Kakap (Lutjanus spp.), Belanak (Valamugil seheli), Yellow Tail (Caesio cuning), Selar Como (Alepes djeddaba), Babu Nyai (Plectorhinchus spp.), Black Bawal (P. niger), White Bawal (P. argenteus), and Ketang-Ketang (Epane punctata). The fat content of the marine catch is between 0,43 - 14,36% and total fatty acids of 0,02-2,26 g / 100 g of fish meat. The results of the second phase of the study, engineering of healthy fish-based snacks carried out in 2 forms, namely modern snacks (13 types) and traditional snacks (11 types). The organoleptic results of the favorite test inform that modern snacks: Bitter ballen and churry burger: very preferred, snacks breaded fish, pastel, scallop, nugget, siomay, fish cakes, burgers, stick fish, and shi kebab: ranged from like to very preferred, fish meatball snacks: ranged from ordinary to like, and ekado: not preferred. While the traditional empek-empek, kroket, lumpia (wet and fried), lemper: ranged from like to very preferred, condro snacks, pastel, arem-arem, onde-onde, otak-otak, and bakwan: ranged from disliked to ordinary.